Relationship between working hours and sleep quality with consideration to effect modification by work style: a community-based cross-sectional study - Aya Yoshida; Keiko Asakura; Haruhiko Imamura; Sachie Mori; Minami Sugimoto; Takehiro Michikawa; Yuji Nishiwaki (Komiyama Printing Co. Ltd, 2024)
Background: Although longer working hours are associated with lower sleep quality, it is still necessary to work a certain number of hours to make a living. In this study, we investigated the relationship between working hours and sleep quality in a community setting. We then explored how to manage work style while maintaining the sleep quality of workers without markedly reducing working hours. Methods: 4388 day-time workers in various occupations living in Ota ward in Tokyo were included in the analysis. The relationship between working hours and sleep quality measured by the Athens Insomnia Scale was examined by ANOVA and linear regression models. Effect modification by work style (work end time, shift in working start and end time, current work from home status, change in work place) on the relationship between working hours and sleep quality was investigated by multivariate linear regression models. Results: Longer working hours were significantly associated with lower sleep quality. The magnitude of the relationship between long working hours and low sleep quality was significantly larger when work end time was later (p for trend of interaction < 0.01) and when working start and end time were shifted later (vs no change, p for interaction = 0.03). The relationship was marginally greater when the proportion of work from home was increased (vs no change, p for interaction = 0.07). Conclusions: A relationship between longer working hours and lower sleep quality was observed among workers. Leaving work earlier or optimizing the work environment at home may diminish the adverse effect of long working hours on sleep quality.